INTEGRATION OF AI IN EDUCATION SYSTEMS: ADDRESSING LEARNING QUALITY GAPS IN REMOTE AREAS - Nurhaliza, Nurhaliza (Asosiasi Persatuan Pengusaha Muda Teknik Informatika, 2025)
The gap in access and quality of education in remote areas is a major challenge for the equitable distribution of education in Indonesia. Uneven technological infrastructure, especially internet access, hinders students in remote areas from getting the same quality of learning as students in urban areas. This study aims to analyze the potential and challenges of artificial intelligence (AI) integration in improving the quality of education in remote areas. Using a qualitative method with a descriptive approach, data were collected through in-depth interviews, field observations, and document analysis from several schools in remote areas. Data analysis was carried out using thematic analysis methods to identify patterns and key findings. The results show that AI has great potential in providing adaptive and personalized learning, despite significant barriers related to infrastructure and policy support. It was also found that effective AI adoption requires government support in the form of inclusive education policies, teacher training, and digital infrastructure improvements. This research recommends a collaborative strategy between the government, the education sector, and the private sector to strengthen the integration of AI as a long-term solution in addressing education gaps in remote areas.